Greenhouse gas emissions resulting from conversion of peat swamp forest to oil palm plantation - Cooper, Hannah V. (Nat Commun, 2020)
Conversion of tropical peat swamp forest to drainage-based agriculture alters greenhouse gas (GHG) production, but the magnitude of these changes remains highly uncertain. Current emissions factors for oil palm grown on drained peat do not account for temporal variation over the plantation cycle and only consider CO(2) emissions. Here, we present direct measurements of GHGs emitted during the conversion from peat swamp forest to oil palm plantation, accounting for CH(4) and N(2)O as well as CO(2). Our results demonstrate that emissions factors for converted peat swamp forest is in the range 70–117 t CO(2) eq ha(−1) yr(−1) (95% confidence interval, CI), with CO(2) and N(2)O responsible for ca. 60 and ca. 40% of this value, respectively. These GHG emissions suggest that conversion of Southeast Asian peat swamp forest is contributing between 16.6 and 27.9% (95% CI) of combined total national GHG emissions from Malaysia and Indonesia or 0.44 and 0.74% (95% CI) of annual global emissions.